Agrarische Organisationsformen für den Binnenmarkt bestimmter Kulturen im Waldgürtel Ghanas - Manshard, Walther (ERDKUNDE, 1957)
The basic industry in Ghana (formerly, the Gold Coast), is agriculture, which is carried on pre dominantly by small peasant farmers. Hitherto, a great deal of work has been devoted to investigating methods and means of production of cash-crops, while the study of the importance of food-farming in the local exchange economy of the country has been, by comparison, neglected. This paper is an attempt to outline briefly the more important aspects under which the system of land rotation, with bush and forest fallow, is organised in the forest belt; special emphasis is given to the important factors of labour, labour migration and land-tenure. The present development of the system of land-tenure towards individual holdings reflects very clearly the spread of social changes from the urban centres of population into the rural areas. There is, for example, the slow change from the traditional matrilineal plural inheritance to a more simple patrilineal system. Insecurity of title and, as a result, constant litigation, are grave problems which could be overcome only by a form of land registration which is not yet a practical proposition. The Huza-System of land purchase and organisation, as practised by the Krobo people in the eastern part of the country, is an interesting feature of Ghana’s agriculture. Here, land is bought in blocks by companies and, later, divided into individual strips. In this way, a comparatively high level of production is achieved and Krobo land is an important food supply area for Accra and its environs. The two most important physiognomic types of agriculture - the mixed forest farm, and the mixed bush farm - are to be found in the scattered food farms of the closed forest zone. A description of these is given, with some mention of the two main techniques of clearing the bush (apam and proka) and with some typical examples of land-use patterns. In a country such as Ghana where political and social progress has outstripped advances in agriculture - on which the economy or the country is based - new forms of agricultural organisation will have to be found in the future. But, for this very reason, it is necessary now to take stock of existing forms. The low standard of efficiency, including the low yields per acre, of the existing system of land rotation makes some reform inevitable. So far, however, past research undertaken in Africa with such an end in view has been as haphazard and as uncoordinated as this system of tropical farming itself.